(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Protein folding design and genomic data processing methods are more powerful tools to investigate the fundamental principle of IoT based healthcare. In previous researches, protein folding has the problem of finding the lowest energy conformation and size complexity. Along with this, there is a security problem in genome sequence and complications in storing genome data due to the unstructured format. To tackle these issues a novel Bilateral conception strategy has been proposed in this paper. Initially, the problems of finding the lowest energy conformation and size complexity have been solved by a novel Reconcile pirouette mechanismbased quantum processor through decrease the quantum circuit from quadratic to quasi-linear. Then, the novel Adumbrating algorithm for secure commune based genomic data analysis deals with the security issue and provides the highest privacy for the genome data by using Single Nucleotide Polymorphisms. Finally, a novel Adroit Semantic web-based system is proposed for securely storing and retrieving genome data by Collateral Description frame format. Thus the novel bilateral conception strategy effectively solves the problem in protein folding and provides a high security and storage format for genome sequence.